Timing and patterns in the taxonomic diversification of Lepidoptera (butterflies and moths). - Niklas Wahlberg (Public Library of Science (PLoS), 2013)
The macroevolutionary history of the megadiverse insect order Lepidoptera remains little-known, yet coevolutionary dynamics with their angiospermous host plants are thought to have influenced their diversification significantly. We estimate the divergence times of all higher-level lineages of Lepidoptera, including most extant families. We find that the diversification of major lineages in Lepidoptera are approximately equal in age to the crown group of angiosperms and that there appear to have been three significant increases in diversification rates among Lepidoptera over evolutionary time: 1) at the origin of the crown group of Ditrysia about 150 million years ago (mya), 2) at the origin of the stem group of Apoditrysia about 120 mya and finally 3) a spectacular increase at the origin of the stem group of the quadrifid noctuoids about 70 mya. In addition, there appears to be a significant increase in diversification rate in multiple lineages around 90 mya, which is concordant with the radiation of angiosperms. Almost all extant families appear to have begun diversifying soon after the Cretaceous/Paleogene event 65.51 mya.